Comparison of spontaneous brain activity in distinguishing parkinsonian variant of multiple system atrophy from Parkinson’s disease at an early stage - Wang, Shichan; Xiao, Yi; Hou, Yanbing; Li, Chunyu; Zhang, Lingyu; Ou, Ruwei; Wei, Qianqian; Lin, Junyu; Yang, Tianmi; Che, Ningning; Jiang, Qirui; Zheng, Xiaoting; et al. (Frontiers in Aging Neuroscience, 2024)
Background The overlapping clinical manifestations in parkinsonian variant of multiple system atrophy (MSA-P) and Parkinson’s Disease (PD) can complicate clinical diagnostic accuracy, particularly in the early stage. The study aims to uncover the patterns of brain function in the initial phase of the two conditions. Methods We recruited 24 MSA-P patients, 34 PD patients and 27 healthy controls (HC). Voxel-wise fractional amplitude of low-frequency fluctuation (fALFF) was compared to characterize regional brain function, followed by seed-based functional connectivity (FC) analysis. Receiver operating characteristic (ROC) analyses were used to examine the diagnostic accuracy of fALFF. Results Compared to HC, decreased fALFF was observed in the bilateral basal ganglia (BG) of MSA-P patients, while decreased fALFF was identified in the left BG of PD patients. Additionally, elevated fALFF was found in the superior cerebellum for MSA-P patients and the temporo-occipital cortex for PD patients. Furthermore, PD patients exhibited increased FC in the cortico-striatal loop compared to MSA-P patients. The fALFF of the left caudate distinguished MSA-P from HC with an area under the curve (AUC) of 0.838 (p < 0.001) and from PD with an AUC of 0.772 (p < 0.001). The fALFF of the left putamen distinguished PD from HC with an AUC of 0.736 (p = 0.002). Conclusion Our findings indicated common and distinct abnormalities in spontaneous brain activity within BG, cerebellum, and cortices in early-stage MSA-P and PD patients. PD patients employed more compensatory mechanisms than MSA-P patients. Furthermore, fALFF may aid in early differentiation between MSA-P and PD.